No longer Singaporean - Leong, Susan (Taylor and Francis, 2011)
From communal politics and internet governance to language policies, the tiny speck that is Singapore is known for doing things its own way, with an innovative if patriarchal government kneading a hungry, migrant mass into one of the most well disciplined, efficient, and diligent working populations in Southeast Asia. Much has also been made of its success at multiculturalism though some, like sociologist Chua Beng Huat, argue it to be multiracialism. Using Chua’s argument as a platform for departure, and taking a cue from Stratton’s notion of ‘everyday multiculturalism’ I argue through a reflexive exploration of Singapore as a lived experience, that rather than conflict, the two theories complement each other with the former paving the way for the latter.